2001
DOI: 10.1108/13620430110389757
|View full text |Cite
|
Sign up to set email alerts
|

Employing organisations and expatriate spouses: balancing self‐knowledge and knowledge about options

Abstract: The context in which careers are being played out has changed and is constantly changing, both in domestic employment settings and more particularly in global business environments. Such international business environments highlight career choices often hidden in domestic situations. It is here that the balance between family and career become tangible. The career costs and benefits of taking an overseas assignment for both partners become open to question. This article considers the situation of the accompany… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Echoing Schermerhorn's (1999) recollections of taking a sabbatical in Malaysia, half of the participants in this study (including some who were single) reported that family played a dominant role in the decision to take an overseas appointment. That the family plays a key role in the decision is a dominant theme in the contemporary expatriate management literature (Anderson, 2001; Forster, 1997; Glanz and Van Der Sluis, 2001; Harvey, 1997). Although this finding adds nothing new to the literature on expatriate managers, its primary value is in pointing out that the family is also an important influence for other types of expatriates.…”
Section: Resultsmentioning
confidence: 99%
“…Echoing Schermerhorn's (1999) recollections of taking a sabbatical in Malaysia, half of the participants in this study (including some who were single) reported that family played a dominant role in the decision to take an overseas appointment. That the family plays a key role in the decision is a dominant theme in the contemporary expatriate management literature (Anderson, 2001; Forster, 1997; Glanz and Van Der Sluis, 2001; Harvey, 1997). Although this finding adds nothing new to the literature on expatriate managers, its primary value is in pointing out that the family is also an important influence for other types of expatriates.…”
Section: Resultsmentioning
confidence: 99%
“…Suutari and Brewster () found that SIEs are more likely to be dual‐income couples and, according to Cole (), recent accompanying spouses tend to be highly educated and experienced professionals. Hence, MNEs should think seriously about such family concerns by offering career advice for accompanying spouses, issuing their work visas, or giving them corporate employment opportunities if their talents and resources match organizational needs (Glanz & van der Sluis, ). Although this may be criticized as nepotistic recruitment, this may be less important, because in many parts of the world nepotism does not matter; rather, hiring one's relatives seems reasonable if considering that many MNEs experience difficulties in pursuing international assignments with limited resources and also dealing with the expatriate failure due to spousal dissatisfaction.…”
Section: Self‐initiated Expatriates (Sies)mentioning
confidence: 99%
“…The centrality of the family's role has led to recommendations that it should also be included in selection and training procedures (Moore, 2002). Furthermore, research on dual‐career couples has given rise to calls for organizations to assist in finding work for accompanying spouses (Glanz and Van Der Sluis, 2001; Moore, 2002; Riusala and Suutari, 2000). A study of repatriated female executives in Australian companies (Anderson, 2001), for example, reported that problems were particularly common among couples where one partner had resigned from a professional position in order to accompany the other.…”
Section: Current Thinking On the Expatriate Familymentioning
confidence: 99%